2013
DOI: 10.1111/1750-3841.12072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Colloidal Structure of Dairy Gels on Milk Fat Fusion Behavior: Quantification of the Liquid Fat Content by In Situ Quantitative Proton Nuclear Magnetic Resonance Spectroscopy (isq 1H NMR)

Abstract: Dairy gels (DG), such as yoghurts, contain both solid and liquid fats at the time of consumption, as their temperature rises to anything between 10 and 24 °C after being introduced into the mouth at 4 °C. The mass ratio between solid and liquid fats, which depends on the temperature, impacts the organoleptic properties of DG. As the ordinary methods for determining this ratio can only be applied to samples consisting mainly in fat materials, a fat extraction step needs to be added into the analytical process w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The formation of dairy gels (e.g., yoghurt) has been investigated by NMR, and an increase in lactate was observed in real time as the microbes fermented the milk, suggesting that the technique may prove useful in the evaluation of new bacterial strains for dairy products [19]. These authors have also demonstrated the utility of NMR for monitoring the changes in liquid fat content in dairy gels, again demonstrating the utility of NMR in understanding complex processes in food processing and production [20]. …”
Section: 1h Nmr Studiesmentioning
confidence: 99%
“…The formation of dairy gels (e.g., yoghurt) has been investigated by NMR, and an increase in lactate was observed in real time as the microbes fermented the milk, suggesting that the technique may prove useful in the evaluation of new bacterial strains for dairy products [19]. These authors have also demonstrated the utility of NMR for monitoring the changes in liquid fat content in dairy gels, again demonstrating the utility of NMR in understanding complex processes in food processing and production [20]. …”
Section: 1h Nmr Studiesmentioning
confidence: 99%